2x+3q+14=0

Simple and best practice solution for 2x+3q+14=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3q+14=0 equation:


Simplifying
2x + 3q + 14 = 0

Reorder the terms:
14 + 3q + 2x = 0

Solving
14 + 3q + 2x = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + 3q + -14 + 2x = 0 + -14

Reorder the terms:
14 + -14 + 3q + 2x = 0 + -14

Combine like terms: 14 + -14 = 0
0 + 3q + 2x = 0 + -14
3q + 2x = 0 + -14

Combine like terms: 0 + -14 = -14
3q + 2x = -14

Add '-2x' to each side of the equation.
3q + 2x + -2x = -14 + -2x

Combine like terms: 2x + -2x = 0
3q + 0 = -14 + -2x
3q = -14 + -2x

Divide each side by '3'.
q = -4.666666667 + -0.6666666667x

Simplifying
q = -4.666666667 + -0.6666666667x

See similar equations:

| 15-2x(4-3x)=37 | | u^2-15u+54=0 | | -(n-5)=-2n-2 | | 5x+2=3+8 | | 20x^2-35x-75=0 | | 4x+3=2x+8findx | | 5*x^2-18*x=-13 | | 5p+7=4(4-p) | | 9x^2-57x+60=0 | | 8x-0.6x^2=-1 | | -29+x=x+26 | | (4x-10/2) | | 7+65x=39x+23 | | 1-1/5x=0.5 | | 16=x-x*0.02 | | -5-2(n+4)=17+4n | | -26-2x=-52+24x | | A=1/7xhz | | x*(-3/4)=18 | | 2x+4-5x=12-15x+12x-8 | | x^2-8*x+15=0 | | x///////////////10=19 | | -4=-3x+2x | | 5x+13=-57-5x | | 33x+3y=-18 | | 2xy^2-2y^2-12xy+12y=0 | | 0.3x-1.5=0 | | a/19=8 | | 4*x^2=20x | | 5n^2-23=0 | | -16-n=4 | | f(x)=x^2y^2-2xy^2-6x^2y+12xy |

Equations solver categories